Perencanaan Perawatan Mesin Conveyor Belt Menggunakan Metode FMEA dan RCM di PT. SBM - Fery Kurniawan; Akhmad Wasiur Rizqi (Universitas Islam Raden Rahmat, Malang, 2025)
PT. SBM is a bulk material handling company that focuses on conveyor maintenance and surface protection. The conveyor belt machine operates 24 hours non-stop resulting in damage to each component which disrupts the production process. So that an analysis is carried out using the FMEA method with the results of the calculation of the RPN value showing that the belt component gets an RPN value of 180, gear of 150, idler roller of 80, and chain of 80. RCM method to determine an effective maintenance strategy with the results of a new activity schedule, namely belt components must be checked and maintained about 4.36 hours/day once and idler rollers about 7.08 hours/day once by performing scheduled on-condition task maintenance activities. Gear must be checked and maintained about 4.12 hours/day once and chain about 0.23 hours/day once by performing scheduled discard task maintenance activities. By applying the results of this research in the company, it can determine a more effective and data-based maintenance schedule with increased machine reliability, maintenance schedule optimization, cost and operational efficiency, and implementation in the manufacturing industry. It is recommended that companies implement IoT-based monitoring systems, conduct training, and establish maintenance standards with periodic evaluation.